2020
DOI: 10.1021/acs.langmuir.0c01109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polypropylene Glycol at Very Low Concentrations on Rheological Properties at the Air–Water Interface and Foam Stability of Sodium Bis(2-ethylhexyl)sulfosuccinate Aqueous Solutions

Abstract: The present study investigates the effects of very low concentrations of polypropylene glycol (PPG) on the rheological properties of sodium bis(2-ethylhexyl)sulfosuccinate (AOT) aqueous solutions at the surface for the precise control of foam properties. Langmuir trough experiments and Brewster angle microscopy (BAM) of the AOT monolayer on the surfaces of PPG aqueous solutions indicated that a very low concentration of PPG increased the number of AOT molecules at the surface. Viscoelastic behaviors at the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In 1994, this method was improved and evaluated as the National Standard of the People's Republic of China GB/T 7462‐94. Studies have shown that the liquid to be tested is preheated in a water bath, then transferred it to a volumetric flask, unscrewed the valve to be tested to flow out and finally recorded the foam volume after a certain period of time (Aono et al ., 2020). Some researchers improved the Ross–Miles method in 2004 (Denkov, 2004).…”
Section: Foaming Properties Of Soy Protein Isolatementioning
confidence: 99%
“…In 1994, this method was improved and evaluated as the National Standard of the People's Republic of China GB/T 7462‐94. Studies have shown that the liquid to be tested is preheated in a water bath, then transferred it to a volumetric flask, unscrewed the valve to be tested to flow out and finally recorded the foam volume after a certain period of time (Aono et al ., 2020). Some researchers improved the Ross–Miles method in 2004 (Denkov, 2004).…”
Section: Foaming Properties Of Soy Protein Isolatementioning
confidence: 99%